2018
DOI: 10.1038/s41416-018-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide comprehensive human papillomavirus (HPV) genotyping of invasive cervical cancer

Abstract: We present one of the largest series of HPV-genotyped cervical cancers to date. The systematic collection of cervical cancer HPV genotyping data by the screening registry will facilitate prevention and monitoring of HPV type-specific disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 16 publications
5
50
0
5
Order By: Relevance
“…In contrast, the Walboomers’ study included predominantly squamous cancers, with a small number of adenocarcinomas and adenosquamous cancers . The Australian figure of 92.9% reported in 2017 aligns with recent studies in other countries which cite figures for the percentage of cervical cancers testing positive for HPV of 92.3% (pooled data worldwide for 2006–2010), 90.6% (United States), and 86.2% (Sweden) …”
Section: Proportion Of Hpv‐positive Cervical Cancers In Australiasupporting
confidence: 63%
“…In contrast, the Walboomers’ study included predominantly squamous cancers, with a small number of adenocarcinomas and adenosquamous cancers . The Australian figure of 92.9% reported in 2017 aligns with recent studies in other countries which cite figures for the percentage of cervical cancers testing positive for HPV of 92.3% (pooled data worldwide for 2006–2010), 90.6% (United States), and 86.2% (Sweden) …”
Section: Proportion Of Hpv‐positive Cervical Cancers In Australiasupporting
confidence: 63%
“…The importance of HPV58 has been investigated by many research groups, and it has been unanimously concluded that HPV58 accounts for a remarkably higher proportion of cervical cancer in East Asia than elsewhere. For instance, HPV58 was found in 29% of HPV‐positive cervical squamous cell carcinomas (SCC) in Shanghai (East China), 21% in Taiwan, 19% in South Korea, 14% in Japan, 13% in south Sichuan (southwestern China), 10% in Hong Kong (east China) and 9% in Yangtze River Delta region (east China) but only 0.6%‐2.8% outside East Asia . HPV58 is therefore the second or third most prevalent HPV type in East Asia, even though it only ranks sixth or seventh worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…Japan, 13 13% in south Sichuan (southwestern China), 14 10% in Hong Kong (east China) 15 and 9% in Yangtze River Delta region (east China) 16 but only 0.6%-2.8% outside East Asia. 17,18 HPV58 is therefore the second or third most prevalent HPV type in East Asia, 3,8,18 even though it only ranks sixth or seventh worldwide. 5 Furthermore, our meta-analysis scrutinising 219 publications from 1994 to 2012 found that attribution of HPV58 to cervical cancer was 3.7-fold higher in East Asia than elsewhere, even after adjustment for bystander effect in multiple-type infections.…”
mentioning
confidence: 99%
“…All samples were HPV genotyped using MGP-PCR, primer targeting L1, and type-specific probes using Luminex detection technology, as previously described (34)(35)(36). Briefly, 5 µL aliquots of extracted DNA were used in the MGP-PCR in a total volume of 25 µL.…”
Section: Mgp-pcr and Hpv Typing Using Luminexmentioning
confidence: 99%